Pendampingan Calistung dan Pembiasaan Shalat Duha bagi Anak Migran Indonesia di Kuala Lumpur Malaysia - Aini, Faradila; Shalihah , Faridatus; Mahsun, Moch; Ulumudin , Ihya; Arifin, Syamsul; Ahmad Ihwanul Muttaqin; Idris , Haidar; Aímah , Syarifatul (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The limited access to formal education experienced by Indonesian migrant children in Malaysia has had a serious impact on their cognitive and spiritual development. These children often lack basic skills such as reading, writing, and arithmetic (Calistung), and receive minimal religious guidance due to their parents' busy work schedules. This study aims to enhance Calistung skills and cultivate the habit of performing Duha prayer through a service-learning approach conducted collaboratively with the Community Learning Center (PKBM) of the Indonesian Embassy in Kuala Lumpur. The subjects consisted of ten first-grade students enrolled in non-formal education. The methods employed included participatory observation, semi-structured interviews, pre-tests and post-tests, and visual documentation. The results showed improvements in the ability to recognize letters, copy names, and perform basic arithmetic operations. The children also began to understand and regularly perform Duha prayer without coercion. This activity demonstrates that service learning can be an effective approach to bridging theory and practice in the field, while also strengthening community engagement in alternative education programs. The main contribution of this initiative lies in the integration of basic literacy development and spiritual character formation as a solution to the educational gap faced by Indonesian migrant children abroad.